Socio-demographic drivers of household food waste management practices in Thailand - Patranit Srijuntrapun; Pattama Ket-um; Witsanu Attavanich (PLoS ONE, 2025)
Objective The escalating food waste crisis, with millions of tons of food being discarded annually, highlights the pressing necessity to improve household food waste management practices. This complex and multifaceted challenge is a crucial element of a comprehensive national strategy for reducing food waste. This article seeks to examine the diverse demographic and social factors that shape household food waste management practices in Thailand. Methods A substantial national dataset (n =  2,500) was meticulously gathered through questionnaires, using multi-stage sampling and multiple regression analysis to reveal critical insights. Results This study reveals that educational attainment (β =  0.299), household size (β =  0.201), and monthly income (β =  0.058) are positively associated with effective household food waste management practices. Notably, the type of housing, such as single houses over 200 square meters (β = .058**) and condominiums/apartments (β = .063**), significantly influence food waste management behaviors. However, townhouses (β =  -.074***) are negatively associated with improved food waste management practices. The research also identifies key barriers to effective food waste prevention, including the lack of organizational guidance (29.4%), the perception that waste reduction does not save costs (26.1%), and uncertainty about where to donate surplus food (25.2%). Additional challenges of managing food scraps include the uncertainty about options for donation or sale of food scraps (43.3%) and the limited knowledge of composting or bio-fermentation methods (30.2%). Conclusions In conclusion, this study provides essential insights for policymakers, practitioners, and researchers by identifying key demographic, knowledge-based, and behavioral factors that shape household food waste management. The study’s findings underscore the need for targeted educational initiatives and infrastructure enhancements. Policymakers can leverage these insights to develop policies that support public-private partnerships and improve waste management infrastructure. Practitioners can apply this knowledge to implement more effective waste segregation strategies, while researchers are encouraged to explore socio-economic factors influencing food waste at a national scale, thereby addressing critical research gaps. This comprehensive approach is vital for reducing household food waste and promoting sustainable waste management practices across diverse communities.